Enhancing behavioral change with motivational interviewing: a case study in a Cardiac Rehabilitation Unit - Pietrabissa, Giada; Ceccarini, Martina; Borrello, Maria; Manzoni, Gian Mauro; Titon, Annamaria; Nibbio, Ferruccio; Montano, Mariella; Bertone, Gianandrea; Gondoni, Luca; Castelnuovo, Gianluca (Frontiers in Psychology, 2015)
Background: psychological interventions in Cardiac Rehabilitation (CR) programs appear relevant in as much they significantly contribute to achieve the goals of rehabilitation, to reduce the risk of relapses and to improve patients’ adherence to therapy. To this aim, Motivational Interviewing (MI) has shown promising results in improving motivation to change and individuals’ confidence in their ability to do so. Objective: the purpose of this article is to integrate theory with practice by describing a 3-session case scenario. It illustrates how the use of MI’s skills and strategies can be used to enhance health. MI may be synergistic with other treatment approaches and it is used here in conjunction with Brief Strategic Therapy (BST). Conclusions: by the use of Motivational Interviewing principles and technique, the patient reported an increase in his motivation and ability to change, developing a post discharge plan that incorporates self-care behaviors. Clinical Implications: Motivational Interviewing may be effective in motivating and facilitating health behavior change in patients suffering from heart failure.